PROVISION OF SUPPLEMENTARY FOOD FOR SASIGO AND BISCUIT IN INCREASING THE WEIGHT OF CHILDREN : A COMPARATIVE STUDY IN NAMBO PRIMARY HEALTH CARE IN KENDARI CITY: Supplementary Food for Children - Rasyid, Mariyatni; Timbul Supodo; Banudi, La (Universitas Mandala Waluya Kendari, 2020)
Background:The prevalence of community nutritional status in the Kendari City area in 2016 was 0.23%. In 2017, the prevalence of nutritional status decreased in 0.13% and then increased in 2018 by 4.67%. in 2019, the prevalence of nutritional status decreased by 2.25% . Thus,Â children under five have nutritional status did not reached the target This study aimed to understand the effect of giving the sasigo and biscuit on increase the childrenâ€™s weight in Nambo Primary Health Care in Kendari City. Methods:The type of research in this research is pre-experimental research with a Pre Test - Post Test design. This research was conducted in the working area of ??Nambo Peimary Health Care, Kendari City. Population were 227 and a sample was Â 67 malnourished toddlers in 2019. Result:Based on the independent sample test output in the Equal Variances Assumed section on Local PMT (BageaSasigo), it is known that the sig (2-tailed) value is 0.001 <0.05, so Ha is accepted so that there is a significant difference between the provision of local PMT (BageaSasigo). Whereas in the Government PMT (biscuits) it is known that the sig (2-tailed) value is 0.000 <0.05, so Ha is accepted so that there is a significant difference between the provision of government PMT (biscuits) to toddlers in the Work Area of ??the PuskesmasNambo, Kendari City. Conclusion:Provision of Local PMT (Bagea Sasigo) and Government PMT (Biscuits) for toddlersBefore giving the intervention it was not effective while after giving the intervention it was effective and significant.